The application of information and communication technology in education science classes - Merjem Rustempašić, Sanela; Livančić, Matej (2021)
This article examines the use of information and communication technology (ICT) in teaching Science as well as the organisation and realisation of online classes during the ongoing COVID-19 pandemic. In respect to this, the research results are used to gather teachers' viewpoints and opinions regarding the application of ICT in Science classes, as well as to determine the best method of application of the aforementioned technologies and the form of ICT most often used in Science classes. The results are also used to gather teachers' opinions about online classes, and to examine the problems and disadvantages the teachers encountered when organising and holding online Science classes for the lower grades of elementary schools in Bosnia and Herzegovina during the COVID-19 pandemic. The results of the research also illustrate that teachers have a positive opinion in regards to the use of ICT in Science classes as well as the frequent (albeit not constant) use of it. The teachers not only consider themselves competent enough to apply all forms of new technologies in their classes, but express the will and motivation for further education related to ICT application as well. On the other hand, teachers do not have a positive opinion about online classes due to the many difficulties they encounter, such as technical issues, inteference by parents, lack of direct contact with students, the inability to monitor their progress and the general deficiency of equipment needed to incorporate ICT into regular classes, as well as other difficulties of a similar nature. However, the research results also show that teachers believe new technologies are connected to the development of new skills and the improvement of students' existing skills.
U ovome se radu razmatra primjena informacijsko-komunikacijskih tehnologija (IKT-a) u nastavi Moje okoline, ali i određeni aspekti koji se vežu za organizaciju i realizaciju online nastave u vremenu pandemije koronavirusom (COVID-19). Istraživački zadaci su pribaviti mišljenje i stavove učitelja o primjeni informacijskokomunikacijske tehnologije u nastavi Moje okoline, odrediti načine korištenja navedenih tehnologija te oblika informacijsko-komunikacijskih tehnologija koji se najčešće rabe u nastavi Moje okoline, ali i pribaviti mišljenje učitelja o online nastavi te razmotriti probleme i nedostatke s kojima su se učitelji susretali prilikom njezine organizacije i realizacije u vremenu pandemije koronavirusom (COVID-19) u nižim razredima osnovne škole u Bosni i Hercegovini. Rezultati istraživanja pokazali su da učitelji u Bosni i Hercegovini imaju pozitivan stav prema informacijsko-komunikacijskim tehnologijama u nastavi Moje okoline i da tu tehnologiju upotrebljavaju često, iako ne konstantno, smatraju se dovoljno kompetentnim za uporabu svih oblika novih tehnologija u nastavi Moje okoline, ali su i motivirani za dodatne edukacije koje se odnose na primjenu IKT-a. Međutim, nemaju pozitivan stav prema online nastavi jer se susreću s mnogim poteškoćama u vidu tehničkih problema, nemogućnosti direktnoga kontakta s učenicima, uvida u napredak učenika i nedovoljnom opremljenosti škola za uvođenje IKT-a u redovnu nastavu, te nedostacima koji su iste ili slične prirode kao i poteškoće. Učitelji ipak, prema rezultatima istraživanja, smatraju da nove tehnologije imaju određenu vezu s razvojem novih i unapređenjem njihovih starih sposobnosti, kompetencija i vještina kod učenika, iako IKT u najvećoj mjeri rabe za izradu prezentacija i gledanje videozapisa s učenicima.
Bibliografija: 27 jed.
Summary ; Sažetak.
Keywords: Informacijsko-komunikacijska tehnologija -- Online nastava -- COVID-19 -- Kompetencije učitelja; Bosna i Hercegovina